Penggunaan Majas oleh Agen Iklan Berbasis Online di Instagram - Umi Agus Fitriani; Razali Razali; Muhammad Iqbal (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This research is titled "The Using of Majas by Online Basic Advertation Agent in Instagram". The problem with this research is how is the use of majors in advertising for beauty, food, and robe products based online by agents on Intagram. The purpose of this study is to find out how the use of majas by advertising agencies based online on Instagram. The data source of this research is the caption or product description in the #kosmetikbandaaceh, #makananbandaaceh, and #gamisbandaaceh tags on Instagram. The method used is a qualitative research method. The data collection technique of this study is the documentary collection technique while the data analysis technique in this study was carried out by sorting data from #kosmetikbandaaceh, #makananbandaaceh, and #gamisbandaaceh; determine how the use of majas in the writing and record who the online business agent is; and draw conclusions by giving a statement on how to use majas by advertising agencies based online on Instagram. The results of the study show that the program used by the advertising agency on Instagram is a comparison, an affirmation, and a contradiction. Majas which include (1) comparative lectures, namely anthropomorphism, aptronym, metonymy, hyperbole, personification, and eponym, (2) confirmation, namely pleonasm, repetition, pararima, climax, tautology, sigmatism, antaclasis, inversion, rhetoric, and ekslamasio, and (3) the form of conflict, namely the antithesis and contradiction of interminus. Furthermore, there are also deviations and errors in the assembly. These deviations and errors are usually related to the use of prepositions, punctuation, italics and capital letters